Sodium–glucose cotransporter-2 inhibitor combination therapy to optimize glycemic control and tolerability in patients with type 2 diabetes: focus on dapagliflozin–metformin - Schwartz SS (Dove Medical Press, 2016)
Stanley S Schwartz,1,2 Arie Katz3 1University of Pennsylvania, Philadelphia, PA, USA; 2Main Line Health System, Ardmore, PA, USA; 3AstraZeneca, Fort Washington, PA, USA Abstract: In type 2 diabetes (T2D), early combination therapy using agents that target a number of the underlying pathophysiologic defects contributing to hyperglycemia may improve patient outcomes. For many patients, the combination of metformin with a sodium–glucose cotransporter-2 (SGLT-2) inhibitor may be a good option because these agents have complementary mechanisms of action, neutral-to-positive effects on body weight, and a low risk of hypoglycemia. This review focuses on the combination of metformin with dapagliflozin, a member of the SGLT-2 inhibitor class of antidiabetes agents. In clinical trials, the combination of dapagliflozin with metformin produced significant and sustained reductions in glycated hemoglobin and body weight in a broad range of adult patients with T2D, including those initiating pharmacotherapy and those with more advanced disease. These reductions were accompanied by modest decreases in blood pressure. Dapagliflozin as add-on therapy to metformin was well tolerated and associated with low rates of hypoglycemia. Genital infections and, in some studies, urinary tract infections were more frequent with dapagliflozin than with placebo. Early combination therapy with dapagliflozin and metformin may be a safe and appropriate treatment option that enables patients with T2D to achieve individualized glycemic goals as either initial combination therapy in treatment-naïve patients or as dapagliflozin add-on in patients inadequately controlled with metformin therapy. Keywords: combination therapy, dapagliflozin, metformin